2013
DOI: 10.4103/0972-2327.116933
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Parkinsonism: An illustrative case report

Abstract: Non-Hodgkin's lymphoma of T-cell types are rare neoplasms. Central nervous system metastasis is unusual. We are reporting a patient with peripheral T-cell lymphoma unspecified who had extra nodal metastasis into the brain that manifested with extrapyramidal dysfunction. The clinical presentation was exceptional in that the course was indolent and patient had no overt extra neural manifestations of malignancy for nearly 3 years after the onset of Parkinsonism. Striking brain imaging late in the disease supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Previous authors who presented cases with Parkinsonism as a symptom of basal ganglia lymphoma suggested interruption of striatal postsynaptic dopamine receptors. 5,6 The unique features of our patient are that she did not have classic MRI findings of a PCNSL but later evolved to classic MRI findings with T1 and T2 FLAIR hyperintesities with homogenous contrast enhancement. 13 Also, her CSF cytology and flow cytometry was negative for lymphoma, but her 14-3-3 protein was elevated with Creutzfeldt-Jakob disease in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous authors who presented cases with Parkinsonism as a symptom of basal ganglia lymphoma suggested interruption of striatal postsynaptic dopamine receptors. 5,6 The unique features of our patient are that she did not have classic MRI findings of a PCNSL but later evolved to classic MRI findings with T1 and T2 FLAIR hyperintesities with homogenous contrast enhancement. 13 Also, her CSF cytology and flow cytometry was negative for lymphoma, but her 14-3-3 protein was elevated with Creutzfeldt-Jakob disease in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…2 Despite the involvement of basal ganglia in CNS lymphomas, only a handful cases have been reported with movement disorders like segmental dystonia, choreoathetosis, and Parkinson's disease. [3][4][5][6][7][8] We presented an unusual case of gradually progressing Parkinsonism with an elevation of CSF 14-3-3 protein and atypical imaging findings found to have PCNSL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation